Perancangan RESTful API Menggunakan Java Quarkus Untuk Modul Mahasiswa Pada Layanan SIMAK-NG Universitas Udayana - I Kadek, Ari Wijaya; Wiharta, Dewa Made; Sastra, Nyoman Putra Putra (Majalah Ilmiah Teknologi Elektro, 2022)
Information systems are very important in today's technological era. The services or methods used to deliver information are always evolving to provide better services. SIMAK-NG Udayana University is an information system built by the Udayana University Resources and Information Unit (USDI) to provide convenience to users (academic operators, lecturers and students) in online academic administration activities, which is Integrated Information System, known as Integrated Management Information System the Strategic of Udayana (IMISSU). Previously built on a monolithic architecture, SIMAK-NG migrate the service architecture to microservices. Therefore, need to customize the program code by implementing a RESTful API that supports the performance of SIMAK-NG service. In this study, the design of a RESTful API model was made This can be used by other applications that require student data from the SIMAK service and access RESTful API services instead of accessing the database directly. API was built using the Java programming language, the Quarkus framework, and a database schema that matched the database at the SIMAK-NG service at Udayana University. The test was run locally and show that the RESTful API program's response results are as designed and work well as shown in the tests using the Postman script. this indicates that the designed API program is ready for implementation.